Complete and long-lasting clinical responses in immune checkpoint inhibitor-resistant, metastasized melanoma treated with adoptive T cell transfer combined with DC vaccination - Lövgren, Tanja; Wolodarski, Maria; Wickström, Stina; Edbäck, Ulrika; Wallin, Mette; Martell, Eva; Markland, Katrin; Blomberg, Pontus; Nyström, Maria; Lundqvist, Andreas; Jacobsson, Hans; Ullenhag, Gustav; et al. (OncoImmunology, 2020)
Development of T cell-directed immune checkpoint inhibitors (ICI) has revolutionized metastatic melanoma (MM) therapy, but <50% of treated patients experience durable responses. This phase I trial (NCT01946373) investigates the safety/feasibility of tumor-infiltrating lymphocyte (TIL) adoptive cell therapy (ACT) combined with dendritic cell (DC) vaccination in MM patients progressing on ICI. An initial cohort (5 patients) received TIL therapy alone to evaluate safety and allow for optimization of TIL expansion protocols. A second cohort (first-in-man, 5 patients) received TIL combined with autologous tumor lysate-loaded DC vaccination. All patients received cyclophosphamide/fludarabine preconditioning prior to, and intravenous (i.v.) IL-2 after, TIL transfer. The DC vaccine was given as five intradermal injections after TIL and IL-2 administration. [18F]-FDG PET/CT radiology was performed to evaluate clinical response, according to RECIST 1.1 (on the CT part). Immunological monitoring was performed by flow cytometry and T-cell receptor (TCR) sequencing. In the safety/optimization cohort, all patients had a mixed response or stable disease, but none durable. In the combination cohort, two patients experienced complete responses (CR) that are still ongoing (>36 and >18 months, respectively). In addition, two patients had partial responses (PR), one still ongoing (>42 months) with only a small bone-lesion remaining, and one of short duration (<4 months). One patient died early during treatment and did not receive DC. Long-lasting persistency of the injected TILs was demonstrated in blood. In summary, we report clinical responses by TIL therapy combined with DC vaccination in 4 out of 4 treated MM patients who previously failed ICI.